2009
DOI: 10.3892/mmr_00000142
|View full text |Cite
|
Sign up to set email alerts
|

BubR1 and AURKB overexpression are associated with a favorable prognosis in gastric cancer

Abstract: Abstract. The majority of human solid tumors exhibit aneuploidy caused by impairment of the mitotic checkpoint. Since the Mad2, Bubr1 and aurora kinase B (aurKB) proteins are involved in the mitotic checkpoint, we investigated Mad2, BubR1 and AURKB mrna expression and its effect on clinicopathological parameters and prognosis in 100 consecutive patients who underwent surgical resection for gastric cancer. Mad2, BubR1 and AURKB mrna expression levels in gastric cancer tissues and corresponding normal gastric mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Various factors appear to play a role in aneuploidy which includes sister chromatid cohesion, abnormal kinetochore structure, mitotic checkpoint dysfunction or centrosome abnormalities. [ 13 ] Impaired SAC function has also been suggested to be one of the common causes of aneuploidy in human cancers. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various factors appear to play a role in aneuploidy which includes sister chromatid cohesion, abnormal kinetochore structure, mitotic checkpoint dysfunction or centrosome abnormalities. [ 13 ] Impaired SAC function has also been suggested to be one of the common causes of aneuploidy in human cancers. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] This aberrant expression plays a significant role in cancer initiation and progression. [ 13 ] Its expression is considered as a marker for poor survival in certain types of human cancer. [ 6 ] Mutation of hBUB1B gene appears to be a rare event in human malignancy supporting the view that BUBR1 overexpression is as a result of up-regulation of the normal gene.…”
Section: Discussionmentioning
confidence: 99%
“…Ando et al, on the other hand, found a significant high correlation between BUBR1 overexpression and DNA aneuploidy [37]. Interestingly, in another study investigating the expression status of BUBR1 and AURKB, the authors concluded that overexpression of BubR1 and AURKB is associated with a low risk of gastric cancer progression [38]. MAD1 and MAD2 are also important regulators of cell cycle progression, involved in alignment of chromosomes at the metaphase plate.…”
Section: Chromosomal Instability (Cin)mentioning
confidence: 99%
“…Up-regulation of AURKB in Epstein-Barr virus- (EBV)-transformed lymphoblasts is correlated with EBV immortalization and tumorigenic ability in vitro [12]. A number of studies discover that high expression of AURKB is associated with unfavorable prognosis of cancers such as acute myeloid leukemia, nasopharyngeal carcinoma, colorectal adenocarcinoma and gastric cancer [1316]. Suppression of AURKB down-regulates phosphorylation of VCP and activates the NF-κB signaling pathway in OS cells, resulting in inhibition of cell proliferation, migration and invasion [17].…”
Section: Discussionmentioning
confidence: 99%